Agrarian inequalities and conflicts - Fernandes, Bernardo Mançano [UNESP] (Taylor & Francis, 2025)
The history of colonization in Latin America has led to inequalities and agrarian conflicts in rural areas. To better understand this process, we use key concepts that explain the times and spaces of the conflicts. These began with the arrival of the colonizer in the 16th century and continue to the present day. Examples of these conflicts include the exploitation of natural resources like mining, agricultural and tree monocultures, and recently, so-called green or clean energies, such as solar and wind power. The production of monocultures, minerals, and energy in the territories of indigenous and peasant populations causes inequality and conflicts because it prevents them from existing on their lands. This process of deterritorialization has been happening throughout Latin America since the 16th century. However, people have built forms of resistance to continue living in their territories, which we demonstrate in the final part of this chapter. There is a special emphasis on the Amazon because it is increasingly the territory most sought after by companies for extractive exploration. But the Amazon has an impact on the atmospheric dynamics of South America, so the destruction of the Amazon Forest impacts the entire continent. It is crucial to think about the occupation of the Amazon from the sustainable understanding of Indigenous peoples. We study this as an example of overcoming that can help mitigate inequalities.